Production and Characterization of Highly Thermostable β-Glucosidase during the Biodegradation of Methyl Cellulose by Fusarium oxysporum - Folasade M. Olajuyigbe; Chidinma M. Nlekerem; Olusola A. Ogunyewo (Biochemistry Research International)
Production of β-glucosidase from Fusarium oxysporum was investigated during degradation of some cellulosic substrates (Avicel, α-cellulose, carboxymethyl cellulose (CMC), and methylcellulose). Optimized production of β-glucosidase using the cellulosic substrate that supported highest yield of enzyme was examined over 192 h fermentation period and varied pH of 3.0–11.0. The β-glucosidase produced was characterized for its suitability for industrial application. Methyl cellulose supported the highest yield of β-glucosidase (177.5 U/mg) at pH 6.0 and 30°C at 96 h of fermentation with liberation of 2.121 μmol/mL glucose. The crude enzyme had optimum activity at pH 5.0 and 70°C. The enzyme was stable over broad pH range of 4.0–7.0 with relative residual activity above 60% after 180 min of incubation. β-glucosidase demonstrated high thermostability with 83% of its original activity retained at 70°C after 180 min of incubation. The activity of β-glucosidase was enhanced by Mn2+ and Fe2+ with relative activities of 167.67% and 205.56%, respectively, at 5 mM and 360% and 315%, respectively, at 10 mM. The properties shown by β-glucosidase suggest suitability of the enzyme for industrial applications in the improvement of hydrolysis of cellulosic compounds into fermentable sugars that can be used in energy generation and biofuel production.